IMPLEMENTASI YURIDIS PERJANJIAN KAWIN DALAM SISTEM HUKUM POSITIF DI INDONESIA - Arief, Hanafi (Syariah: Jurnal Hukum dan Pemikiran, 2015)
Marital agreement is part of the ?eld of family law which must comply with the provisions of Book I of the Civil Code (BW) Setting of the marriage covenant in the Book of the Civil Code Act is described in Part VII of the Civil Code Article 139 s / d 154. Broadly speaking, marital agreements are binding the party / bride in case of marriage. Based on Article 139 of the Civil Code (BW), the existence of the agreement to marry is as an exception of provision of Article 119 of the Civil Code, namely when the marriage takes place then legally valid rounded unity between the wealth of the husband and wife or in other words the extent set. Article 139 of the Civil Code contains a principle that the prospective husband and wife are free to determine the contents of the marriage covenant they made. However, these freedoms are limited by some restrictions that must be considered by a prospective husband and wife who will make a covenant marriage. The substance of the agreement is not contrary to public order (openbareorde), decency, and religious law.